Editorial: neurotrauma and repair: from peripheral to central nerve injury - Younsi, Alexander (Frontiers in molecular neuroscience, 2023)
Neurotrauma, encompassing traumatic brain injury (TBI), peripheral nerve injury (PNI), and spinal cord injury (SCI), continues to be a major global public health concern. The complex pathophysiological mechanisms and lifelong neurological deficits associated with neurotrauma emphasize the urgent need for effective clinical interventions. The research topic "Neurotrauma and Repair: from Peripheral to Central Nerve Injury" brought together a diverse group of 58 authors, fostering interdisciplinary collaboration, and offering new insights into the multifaceted landscape of neurotrauma research.This collaborative effort yielded a body of work that has garnered significant attention within the scientific community, underscoring the importance of the research contributions and the demand for advances in neurotrauma understanding and treatment."Effects of a Neurokinin-1 Receptor Antagonist in the Acute Phase after Thoracic Spinal Cord Injury in a Rat Model" delves into the potential therapeutic effects of neurokinin-1 receptor antagonists on neuroinflammation and edema following SCI. While the study suggests limited impact on reducing edema, it demonstrates a notable reduction in T-lymphocyte invasion and apoptotic cell numbers with the treatment. Additionally, it hints at a trend towards reduced fibrinogen leakage, endothelial and microglial activation, chondroitin sulfate glycosaminoglycan deposition, and astrogliosis. Although general locomotion recovery remained modest, the C...